Quality management : patients reflections on health care at outpatient clinic of internal medicine department - Ljubičić, Neven (Array, 2009)
Abstract: Middle and older age group relative share in the community permanently grows. Those are commonly burdened with several chronic health conditions or elevated incidence of acute ones and in more frequent need for consulting health services. In the era of modern technical medicine, it is important to increase quality of services particularly patients orientated. Department of Internal medicine developed questionnaire to assess reflections on medical care from the receiver of medical services point of view. Sample was formed from individuals that visited outpatient triage Unit (OTU) and voluntary enrolled, during period April 1 – August 31 2008 for any medical reason. Study population structure had similarly equally of both genders, socio-economical background, and was in age range 18–87. Questionnaire was developed by team of experienced personnel covering satisfaction on received medical care. There were 279 returned formulary in a sample of 6700 patients (4.18%).